Does Capital Intensity have Effect on The Relationship Good Corporate Governance and Tax Aggressiveness? - Zahra, Ananda Fitria (EAJ (Economic and Accounting Journal), 2023)
This study aims to determine the effect of good corporate governance measurement with independent commissioners and institutional ownership on tax aggressiveness. Capital intensity is a moderating variable in companies listed on the Indonesia Stock Exchange, with total assets exceeding $10 trillion from 2017 to 2021. A sample of 65 companies was obtained using the purposive sampling method. The panel regression analysis method was used for the analysis. The finding of this study state that independent commissioners and institutional ownership have no significant effect on tax aggressiveness. Besides, capital intensity cannot moderate the effect of independent commissioners and institutional ownership on tax aggressiveness. The results of this study are expected to benefit the company and later can be an additional consideration not to tax aggressiveness.